The Capabilities of Digital Marketing in Supporting Corporate Sustainability: A Systematic Literature Review - Paramitha Hikmah Rimaningtyas; Izzan Arimi; I Made Sukresna; Hersugondo Hersugondo (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The increasing adoption of digital technologies and sustainability-oriented business strategies has encouraged organizations to integrate digital marketing capabilities into their long-term value creation processes. This study analyzes the contribution of digital marketing capability to corporate sustainability and financial performance in the banking and manufacturing sectors. The study applies a systematic literature review method based on the PRISMA 2020 protocol. This study selected and synthesized 23 eligible articles published between 2020 and 2026 through identification, screening, eligibility assessment, and inclusion stages. Quality appraisal was conducted using the JBI Critical Appraisal Tool to assess methodological relevance and credibility. The synthesis shows that digital marketing capability has developed from a promotional function into a strategic capability that strengthens data utilization, stakeholder engagement, ESG communication, and sustainable value creation. In the banking sector, fintech adoption and digital banking improve operational efficiency, reduce cost pressure, and strengthen institutional resilience. In the manufacturing sector, digital marketing capability supports green supply chain management, green innovation, and sustainable brand positioning. The findings indicate that digital capability, sustainability integration, and ESG transparency strengthen profitability, firm value, and long-term competitive advantage. This study develops an integrated conceptual understanding based on Resource Orchestration Theory, Stakeholder Theory, and Signaling Theory.